ANALISIS KEPUASAN MAHASISWA TERHADAP PENGGUNAAN INTERNET BANKING REFERENSI DARI PERGURUAN TINGGI (STUDI KASUS: PERGURUAN TINGGI DI KOTA SURABAYA) - DINY PUTRI LARAS S.; Sugeng Hariadi; Eko Walujo Suwardyono (Perpustakaan Universitas Surabaya, 2020)
The purpose of this study is to find out whether the students who have owned and used internet banking service facilities from banks that have been determined by the college really feel the satisfaction caused by the efficient level, benefits and security of the internet banking usage. And is it true that efficiencies, benefits and security together have a causal relationship to the level of student satisfaction in the use of internet banking services from banks that have been determined by the college. Questionnaires distributed to respondents are limited only to students in private universities ie universities surabaya who have experience at least 1 year using internet banking. While the sampling using accidental sampling method. The results showed that all the students who own and use internet banking service facility feel satisfaction based on the causal relationship by each of 3 object that is efficient, benefit and security with significant level less or equal to alfa 5%. Except, the object of benefit is significant at alpha 5.2%. And together these three objects are efficient, benefits and security provide a significant positive relationship to the level of student satisfaction as consumers of internet banking service users of the banks that have been suggested by the college.